Evaluation of Malaria and Typhoid Coinfection Among Patients at Yola General Hospital, Adamawa State - Isaac John Umaru; Ingwu Joseph Akem; Solomon O. Asare; Tyem Lawal Danjuma; Usenobong Morgan Akpan; Julius Ishaya Salman; Hauwa A. Umaru; Maryam Usman Ahmed (African Journal of Medicine, Surgery and Public Health Research, 2026)
Although malaria and typhoid fever remain highly prevalent in sub-Saharan Africa, evidence on the prevalence and clinical profile of coinfection in northeastern Nigeria remains limited. This study evaluated the burden and characteristics of malaria and typhoid coinfection among febrile patients attending Yola General Hospital in Adamawa State. A cross-sectional design was employed involving 300 patients presenting with febrile illness. Data were collected through structured questionnaires and laboratory diagnostics. Malaria was diagnosed using rapid diagnostic tests and microscopy, whereas typhoid fever was assessed using the Widal test and blood cultures. Demographic, clinical, and behavioral data were analyzed using descriptive statistics and chi-square tests to identify significant associations. The findings showed that 102 patients (34%) had malaria only, 78 (26%) had typhoid only, and 54 (18%) were coinfected. Coinfection was most prevalent among individuals aged 21–40 years (55.6%) and was slightly more common in males (55.6%) than females (44.4%). The most frequently reported symptoms among coinfected patients were fever (100%), headache (88.9%), abdominal pain (77.8%), and diarrhea (66.7%). Behavioral risk factors, including inconsistent mosquito net use, poor hand hygiene, and consumption of untreated water, were significantly associated with infection. Coinfection rates also peaked during the rainy season from June to September, accounting for 74.1% of cases. The study concludes that malaria and typhoid coinfection constitutes a substantial clinical and public health burden in Yola. These findings contribute empirical evidence on the demographic, symptomatic, behavioral, and seasonal profile of coinfected patients and highlight the need for dual diagnostic screening, improved laboratory infrastructure, and targeted health education on hygiene and vector control.